Improved Hole Extraction and Band Alignment via Interface Modification in Hole Transport Material-Free Ag/Bi Double Perovskite Solar Cells - Schmitz, Fabian; Bhatia, Ribhu; Burkhart, Julian; Schweitzer, Pascal; Allione, Marco; Gallego, Jaime; Piotrowski, Piotr; Cajzl, Jakub; Paszke, Piotr; Mohan Das, Gour; Pawlak, Dorota A.; Bella, Federico; et al. (My University, 2024)
Within one decade, lead halide perovskite solar cells have reached power conversion efficiencies (PCEs) compatible with that of silicon solar cells. While in the beginning, they suffered from short device lifetimes, those have also been strongly improved over time. However, their content of toxic lead still poses a risk of environmental pollution and human health on exposure. The double perovskite (DP) Cs2AgBiBr6 offers the potential to be a lead-free alternative light-harvesting material. Herein, the fabrication of hole transport material (HTM)-free Cs2AgBiBr6-based solar cells is presented, in which the DP surface is modified via a n-butylammonium posttreatment to create a 2D/3D mixed interface. Additionally, the commonly utilized metal electrode and HTM are substituted with a carbon black back electrode (CBE) consisting of up-cycled biowaste. Through the 2D/3D interface modification, charge recombination is suppressed, and band alignment is improved at the perovskite/CBE interface. Additionally, density functional theory calculations reveal that an increasing 2D modification thickness enhances the probability for holes in Cs2AgBiBr6 to be located close to the perovskite/CBE interface, further supporting their extraction. Overall, the PCE of the HTM-free solar cells is improved through the implementation of a low-cost and end-of-waste fabrication strategy.
Keywords: ddc:540